2013
DOI: 10.1590/1414-431x20122603
|View full text |Cite
|
Sign up to set email alerts
|

Plasmatic ADAMTS-13 metalloprotease and von Willebrand factor in children with cyanotic congenital heart disease

Abstract: Changes in plasma von Willebrand factor concentration (VWF:Ag) and ADAMTS-13 activity (the metalloprotease that cleaves VWF physiologically) have been reported in several cardiovascular disorders with prognostic implications. We therefore determined the level of these proteins in the plasma of children with cyanotic congenital heart disease (CCHD) undergoing surgical treatment. Forty-eight children were enrolled (age 0.83 to 7.58 years). Measurements were performed at baseline and 48 h after surgery. ELISA, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Potential contributors to this consumptive process include thrombin and plasmin, which have both been shown to cleave ADAMTS13 and would intermittently increase in the period after injury . Furthermore, ADAMTS13 activity has been associated with bleeding events both in patients with sepsis and in pediatric patients with congenital heart disease undergoing surgery . Additional work, both in animals and in humans, is needed to understand the causal mechanism by which ADAMTS13 activity contributes to TIC.…”
Section: Discussionmentioning
confidence: 99%
“…Potential contributors to this consumptive process include thrombin and plasmin, which have both been shown to cleave ADAMTS13 and would intermittently increase in the period after injury . Furthermore, ADAMTS13 activity has been associated with bleeding events both in patients with sepsis and in pediatric patients with congenital heart disease undergoing surgery . Additional work, both in animals and in humans, is needed to understand the causal mechanism by which ADAMTS13 activity contributes to TIC.…”
Section: Discussionmentioning
confidence: 99%
“…Soares et al reported lower levels of ADAMTS-13 antigen and activity in children with cyanotic CHD prior to surgical correction vs. controls. However, neonates were not included in the study [46]. Diminished ADAMTS-13 levels are probably attributed to elevated VWF levels, leading to consumption of ADAMTS-13, while liver dysfunction is an adding factor.…”
Section: Discussionmentioning
confidence: 99%
“…I helped to establish and characterize a novel VWF:CB assay for the measurement of VWF activity. 223 Soares et al 224,225 employed a VWF:CB to help characterize ADAMTS13 and VWF level and activity in children with cyanotic congenital heart disease. Hugenholtz et al 226 included a VWF:CB to highlight an unbalance between VWF and ADAMTS13 in acute liver failure; in these patients, VWF:Ag was raised, but VWF:CB and VWF:RCo/Ag ratio was reduced, as was ADAMTS13 and the proportion of HMWM.…”
Section: The Next Decade-the 2010smentioning
confidence: 99%